2023
DOI: 10.3389/fddev.2023.1095181
|View full text |Cite
|
Sign up to set email alerts
|

Molecular distribution in intradermal injection for transfer and delivery of therapeutics

Abstract: Intradermal (ID) injection is a technique widely used in laboratorial and clinical applications. The boundary of the dome-like bleb formed during injection is assumed to represent the lateral extent of the injected material. This work systematically characterizes cargo molecule distribution (puddle) as a function of injection volume and molecular/particle size in rat skin post ID injection. In general, results indicate that the puddle forms a subdomain laterally contained within the bleb, with an area inversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Thus, bleb formation, although it is a visual sign of successful ID injection, might not be the best indicator for the success of injection due to the different variables that affect the bleb formation, shape, and diameter. This is also in line with the findings of Lallow et al [34] who also demonstrated that the puddle (distribution of the liquid in the skin) is more important than the shape and formation of the bleb.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, bleb formation, although it is a visual sign of successful ID injection, might not be the best indicator for the success of injection due to the different variables that affect the bleb formation, shape, and diameter. This is also in line with the findings of Lallow et al [34] who also demonstrated that the puddle (distribution of the liquid in the skin) is more important than the shape and formation of the bleb.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with previous observations demonstrating that DNA cargo typically remains within the bleb area. [41] Spatial expression pattern is correlated to strain pattern Results of the numerical simulations demonstrate a correlation between the tissue strain and GFP expression patterns. Figure 3C shows three-dimensional images of COMSOL simulation of negative-pressure application on the tissue model surface.…”
Section: Expression Area and Pattern Is Dependent On Nozzle Sizementioning
confidence: 88%
“…These results allude to important considerations in using suction as a means of enhancing expression following primary ID injection. Our prior study [41] revealed that cargo for ID injection was contained within the visible bleb, especially for macromolecules such as DNA. Therefore, although in general tissue strain does scale with nozzle size for the same suction pressure, larger nozzles have limited benefits as they enclose areas greater than the bleb (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was demonstrated that S. aureus mutants lacking FnBPB or ClfB had a reduced ability to adhere to the skin of patients with atopic dermatitis (AD) 35 . So far, one of the major challenges in traditional bacterium-directed chemotherapies lies in the crisis of antibiotic resistance, which has led to increasing interest in designing antibacterial strategies associated with host microenvironments to enhance antibiotic efficacies [36][37][38][39] . As a matter of fact, it has been reported that biomechanical microenvironments around host cells can exert a crucial impact on bacterial-cell interactions such as binding of adhesins to host cell receptors 40 and bacterial infection of epithelial cells and intracellular accumulation of antibiotics 41 .…”
Section: Introductionmentioning
confidence: 99%